Huntington's disease: Dancing in a dish - Zhang, Kejing (Nature Publishing Group, 2012)
In a recent landmark paper, the Huntington's disease (HD) iPSC Consortium reports on the establishment and characterization of a panel of iPSC lines from HD patients, and more importantly, the successful modeling of HD in vitro. In the same issue of Cell Stem Cell, An et al. reports on the successful targeted gene correction of HD in human iPSCs. Both advances are exciting, provide new resources for current and future HD research, and uncover new challenges to better understand and, most importantly, treat this devastating disease in the near future.